BEREMPATI TERHADAP BUKU FISIK SEBAGAI PENGGAGAS WADAH PEMINATAN AKTIVITAS MEMBACA - Maulidani, Rahmat; Sutanto, Agustinus (Jurusan Arsitektur dan Perencanaan, 2024)
Physical books are an important part of the development of a civilization, history has repeatedly shown the huge impact of knowledge, ideas, and information that was spread directly starting from the era of Mesopotamia, Ancient Greek, Baghdad, Renaissance, and continuing until the present day. Indonesia has a stigma of low interest in reading, but socio-culture is not a natural thing but something systematic and created slowly. Pondok Cina Station has a history of causing hundreds of scholars to demonstrate and hold up KRL due to the eviction of 35 secondhand book stalls to modernize the station. A strong inner bond between scholars and literature is a reminder that physical books are not dead and need to be studied to achieve quality and widely useful socio-culture. Secondhand Bookstore and Physical Books are closely related to various educational institutions, apart from their cheap prices, they also have easy access to read the books beforehand. Secondhand Bookstore become an interesting opportunity in an empathetic movement that pays attention to one of human primitive abilities, namely cognitive. Empathizing with Secondhand Bookstores and Physical Books aims to find and examine the sweet spot that can provide a place that encourages users to be interested in literature, by using the heterotopia design method and emptiness (suwung) philosophy to give birth to a place that ignites a new culture that can be developed systematically and progressively to achieve a new era of literature. Keywords: Architecture; Bookstore; Empathy Architecture; Heterotopia; Physical Books Abstrak Buku fisik merupakan bagian penting dalam perkembangan sebuah peradaban, sejarah telah berulang kali menunjukkan dampak besar dari pengetahuan, ide, dan informasi yang disebarkan secara langsung mulai dari era Mesapotomia, Yunani Kuno, Baghdad, Renaisans, dan terus begitu hingga masa kini. Indonesia memiliki stigma minat membaca yang rendah, namun sosio-kultur bukanlah hal yang natural melainkan sesuatu yang sistematis dan diciptakan secara perlahan. Stasiun Pondok Cina memiliki sejarah yang membuat ratusan mahasiswa berdemo dan menahan KRL akibat penggusuran 35 kios buku bekas untuk modernisasi stasiun. Sebuah ikatan batin yang kuat antara mahasiswa dan literasi menjadi sebuah pemantik bahwa buku fisik belum mati dan perlu dikaji untuk menggapai sosio-kultur yang berkualitas dan bermanfaat secara meluas. Toko Buku Bekas dan Buku Fisik sangat erat hubungannya dengan berbagai lembaga pendidikan, selain karena murahnya harga juga karena mudahnya akses untuk langsung membaca sebelum membeli. Toko Buku Bekas menjadi sebuah peluang dalam gerakan empatik yang merangkul sekaligus memperhatikan salah satu kemampuan primitif manusia yaitu kognitif. Berempati terhadap Toko Buku Bekas dan Buku Fisik bertujuan untuk mencari dan menelisik titik manis yang dapat menghadirkan wadah yang mendorong penggunanya untuk tertarik dengan literatur, dengan menggunakan metode desain heterotopia dan filsafat suwung untuk melahirkan sebuah wadah pemantik kultur baru yang dapat berkembang secara sistematis dan progresif untuk menggapai era literatur yang baru.